Effectiveness of Integrative Couple Therapy on Sexual Function, Marital Intimacy, and Impulsivity in Women Affected by Marital Infidelity - Nezamalmolki, Mitra; Bahrainian, Seyed Abdolmajid; Shahabizadeh, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: One of the most significant factors that can disrupt family health is the breaking of commitment and exclusivity in emotional and sexual relationships and the creation of extramarital relationships, namely marital infidelity. This study aimed to determine the effectiveness of integrative couple therapy on sexual function, marital intimacy, and impulsivity in women affected by marital infidelity. Materials and Methods: This study was a quasi-experimental research with a pre-test, post-test, and three-month follow-up design, accompanied by a control group. The study population included all women affected by marital infidelity who sought help from Yarigar and Organic counseling centers in Tehran during the first six months of 2023. According to the counseling centers’ officials, the total number of these individuals was 93. The study sample consisted of 30 women affected by marital infidelity who referred to counseling centers in District 2 of Tehran in 2023, selected through purposive sampling and then randomly divided into experimental and control groups. Data were collected using the Marital Intimacy Scale, the Barratt Impulsiveness Scale, and the Female Sexual Function Index. In this study, the experimental group underwent emotion-focused therapy in 9 sessions (one 90-minute session per week). Data were analyzed using repeated measures analysis of variance and SPSS software version 22. Findings: The results showed that integrative couple therapy effectively increased sexual function (F=54.5, P<0.001), marital intimacy (F=9.00, P<0.001), and decreased impulsivity (F=7.09, P<0.001) in women affected by marital infidelity. Conclusion: It can be concluded that integrative couple therapy is effective in improving sexual function, marital intimacy, and impulsivity in women affected by marital infidelity and can be used to reduce the psychological problems of these women.